School political culture. What is it and how to study it? - Kamecka-Antczak, Celina (Kultura-Społeczeństwo-Edukacja, 2020)
The article is an attempt to create a new category in the study of the school, which is school political culture. Theoretical meta-analysis was used. In the first part, the author explains why she asks about school political culture. Based on the assumption that the school is an organisation, it justifies applying the tools of political culture to its study. The school as an organisation is a separate system of activity, with clearly defined goals, a specific division of labour among members of the school community and connectivity between elements with a certain degree of formalisation and hierarchy of power. A comparison of elements of the school’s organisation with the basic elements of the political system is presented. The second part introduces the criteria that the theory of political culture should meet to become a theory that can be applied in school space. A meta-analysis of selected concepts of political culture: Gabriel Almond, Vilfredo Pareto and Zbigniew Blok (based on the developed criteria) allowed the selection of a leading theory. The results of meta-analysis are the subject of the third part of the article. The initial adaptation of the selected theory leading to the school specificity is a contribution to further scientific work on the development of a research tool allowing the classification of school political culture: of individual students, as well as the one dominating in the group.